Journal of Environmental Extention (2005)
The study explored the contributions of Jos Wildlife Park towards conservation edtf at'°n !" Plateau State, Nigeria. Data for the study were collected through observation, review o re , oral interview and structured questionnaires. Data obtained were analysed using escrip i statistics in the form of tables, frequency of counts and percentages. A total of 100 questionnaire were administered. Results showed that 90% and 9% of the respondents were students and teachers respectively. 44% and 31% became aware of the park through students and teachers respec ive y while 21% knew of the park through electronic media. 68% and/or 79% visited the park purpose y to see animals and learn respectively. 72% and 12% of the respondents indicated that° ^ e™'fnhg wildlife species and conservation lectures were the peak of their enjoyment in the park. 81 ^ o e respondents prefer being conducted round the park by tour guides to ensure that learning is incorporated. 94% of the respondents are willing to visit the park again. The study further showed that the number of educational visitors increased progressively from 3,844 in the year 1998 to 14,838 in the year 2001. Also, the study revealed that visitors who crave to observe and learn about endangered, threatened, rare and abundant species of wildlife and their environments flock the Jos Wildlife Park on daily basis. Suggestions on how to sustain continuous conservation education were made.